'Venomous' bites from non-venomous snakes : a critical analysis of risk and management of 'colubrid' snake bites /.: a critical analysis of risk and management of 'colubrid' snake bites /. (2011) - Weinstein, Scott A; Warrell, David A; White, Julian; Keyler, Daniel E
No abstract available